Veneração e fé: viver entre lutas, resistências e milagres na floresta Amazônica 1970 - 2010 - Assis, Francisco Pinheiro de (2013)
This work aims at investigating the devotional trajectory of rubber tappers from the Acre River Valley, who managed to re-signify in the course of many decades the popular devotion brought from the Brazilian northeastern region, producing new meanings for their lives through faith. It seeks to show the importance of faith and devotion of hundreds of devotees who inhabit the forests and towns in the Acre River Valley. It also intends to present the various manners those rubber tappers have found to overcome daily difficulties, such as diseases, dangers in the forest, attacks by poisonous animals, and falls from trees or bridges. This research, though grounded in popular religiousness, shows the fragility or the mere state of abandonment of the in-forest inhabitants, and it thus justifies the search to understand the reasons that lead them to turn to faith and popular devotion in order to find ways to overcome daily difficulties and the absence of government assistance. It entertains the hypothesis that those devotees find meaning and reason to life through their faith in Santa Raimunda (Saint Raimunda), and in the protection She offers. Interviews and direct contacts with them during pilgrimages in the varadouros (small roads in rubber plantations), beads, and homage at Santa Raimunda´s tomb gave us the opportunity to gather rich and important data. The results show that the devotion to Santa Raimunda do Bom Sucesso (Saint Raimunda of Good Success) kept and still keeps the devotees men and women ready for their daily struggles, giving meaning to their lives and renewing their hopes. Devotion provided them strength to live in the rubber plantations as long as possible, and continues to support their lives in the periphery of the capital city of Rio Branco